Key floral-fruity aroma compounds in Sichuan Congou black tea: identification via MDGC-MS/O and sensory evaluation - Wang, Sixuan; Li, Luorui; Meng, Qing; Luo, Wei; Wei, Fang; Luo, Liyong; Zeng, Liang (Frontiers in Nutrition, 2025)
Congou black tea has garnered significant interest among customers because of its distinctive floral-fruity aroma. To determine the differences in characteristic volatile compounds among various varieties, a total of 147 volatile compounds were identified across 25 samples via gas chromatography–mass spectrometry (GC-MS). Through hierarchical clustering analysis (HCA), 25 samples were classified into two clusters, in which the Fuding variety, Jinguanyin variety, Huangguanyin variety, and Meizhan variety were clustered into one category, whereas the Sichuan population variety was clustered into the other. These two categories were further analyzed via orthogonal partial least squares discriminant analysis (OPLS-DA), and 48 differential compounds were identified. The Sichuan population variety was found to contain a higher concentration of floral and fruity aroma compounds while exhibiting fewer green or grassy odor compounds. To explore the floral-fruity aroma components of Sichuan Congou black tea (SCBT), forty-nine aroma-active compounds were identified through multidimensional GC–MS/olfactometry (MDGC-MS/O). Among them, six components with odor activity values (OAVs) ≥1 were regarded as key floral-fruity aroma components. Recombination and omission tests ranked the contributions of these compounds as follows: geraniol, linalool, methyl salicylate, benzeneacetaldehyde, beta-myrcene and benzaldehyde. Addition experiments confirmed for the first time that linalool, beta-myrcene and methyl salicylate are the key citrus-like compounds, offering valuable insights for the exploration of germplasm resources and quality control of black tea with special aromas.